Color-Coded Cerebral Computed Tomographic Angiography. Issue 5 (May 2015) - Thierfelder, Kolja M.; Havla, Lukas; Beyer, Sebastian E.; Ertl-Wagner, Birgit; Meinel, Felix G.; von Baumgarten, Louisa; Janssen, Hendrik; Ditt, Hendrik; Reiser, Maximilian F.; Sommer, Wieland H.
<x xml:space="preserve">Abstract</x> Objective The objective of this study was to develop a new method of displaying dynamic cerebral computed tomographic (CT) angiography (CTA) data sets in which the time delay to maximum enhancement (Tdelay) is displayed in a range of colors (color-coded CT angiography [cCTA]). Materials and Methods This institutional review board-approved study included multiparametric CT data sets from 16 patients with different types of supra-aortic large vessel occlusions. Color-coded CT angiography was reconstructed from CT perfusion raw data sets. All voxel enhancement curves were fitted to f(t) = α · AIFmtt(t − Δt), with AIFmtt(t), indicating enhancement of AIF dilated by convolution with boxcar function (with mean transit time [mtt]); α, scaling factor; and [INCREMENT]t, transition along the time. The time delay to maximum enhancement was defined as Tdelay = Δt +0.5 · mtt. Values of Tdelay were color-coded and superimposed on temporal maximum intensity projections CTA resulting in colored angiographic composite images. For a pilot clinical evaluation, diagnostic confidence in determining the pathology, quality of the visualization of leptomeningeal collaterals, and additional diagnostic information were assessed. Results The reconstruction of cCTA was technically feasible in all 16 patients. Both diagnostic confidence (P < 0.01) and the quality of the visualization of collaterals (P < 0.0001) were significantly higher when using the combination of single-phase CTA and cCTA compared with single-phase CTA alone. Additional diagnostic information was obtained with cCTA regarding occlusion type (reader 1: 5 cases and reader 2: 4 cases), differentiation between arteries and veins (11/13), differentiation between antegrade and retrograde filling (12/13), as well as leptomeningeal collateralization (13/14). Conclusions Color-coded CT angiography is a technically feasible technique that provides additional information on cerebral hemodynamics in ischemic stroke patients.